Development and survival of neurons in dissociated fetal mesencephalic serum-free cell cultures: I. Effects of cell density and of an adult mammalian striatal-derived neuronotrophic factor (SDNF) - Dal Toso, R (J Neurosci, 1988)
The use of CNS cultures for detection and quantification of neuronotrophic activity in the CNS has been analyzed. In particular the development, i.e., neurotransmitter uptake characteristics, and survival of dopaminergic and GABAergic neurons in fetal mouse (E13)- dissociated mesencephalic cells cultured in serum-free, hormone- supplemented medium have been assessed as a function of culture time and cell density. At all times, more than 98% of the cells were classified as neurons on the basis of immunocytochemical criteria. Results indicate that the increase of cell density in vitro significantly enhances specific high-affinity dopamine uptake per dopaminergic cell and cell survival. This effect is not limited to the dopaminergic cells and suggests that the development of neurotransmitter-related traits and cell survival are influenced by cell density-derived trophic signals. The above-mentioned cultures and parameters have also been used to detect neuronotrophic activity in adult mammalian brain extracts or more purified preparations. In particular, bovine striatal extracts contain activity capable of increasing high-affinity neurotransmitter uptake parameters and cell survival of at least the dopaminergic and GABAergic neurons present in the culture system. The neuronotrophic activity from bovine striatum has been partially purified and is associated with a fraction whose main component is a basic protein of approximately 14 kDa.